(untitled) (World Bulletin of Education and Learning, 2025)
The integration of creative and digital approaches in training future primary school teachers enhances their professional readiness and adaptability. Creative methods encourage imagination, problem-solving, and flexible thinking, while digital tools support interactive learning, collaboration, and innovative teaching practices. Combining these approaches helps prospective teachers design engaging lessons, use modern educational technologies, and meet diverse learners’ needs. This synergy also develops digital literacy, pedagogical creativity, and the ability to create student-centered learning environments. As a result, future teachers become more competent in applying blended learning, digital storytelling, gamification, and project-based methods. Such integration prepares them for contemporary educational challenges and fosters meaningful learning experiences for young pupils.